Demographic and clinical profile of oral lichen planus: A retrospective study - Anita D Munde; Ravindra R Karle; Pranali K Wankhede; Safia S Shaikh; Meena Kulkurni (Wolters Kluwer Medknow Publications, 2013)
Introduction: Oral lichen planus (OLP) is a relatively common inflammatory mucocutaneous disorder that frequently involves the oral mucosa. The clinical presentation of OLP ranges from mild painless white keratotic lesions to painful erosions and ulcerations. An important complication of OLP is the development of oral squamous cell carcinoma, which led the World Health Organization (WHO) to classify OLP as a potentially malignant disorder. The demographic and clinical characteristics of OLP have been well-described in several relatively large series from developed countries, whereas such series from developing countries are rare. Objective: The objective of this retrospective study was to investigate the epidemiological and clinical characteristics of 128 OLP patients in rural population of India. Materials and Methods: In this study, the diagnostic criteria proposed by van der Meij et al. in 2003 based on the WHO definition of OLP were used to identify cases. Results: In 128 patients, M:F ratio was 1.61:1. The buccal mucosa was the most common site (88.20%). White lichen was seen in 83.59% and red lichen in 16.40% cases. Reticular type of OLP was the most common form (83.5%) followed by erosive (15.6%) and atrophic OLP (0.78%). The incidence of systemic diseases included hypertension (11%), diabetes mellitus (2.4%), and hypothyroidism (0.78%). Histopathologically epithelial dysplasia was present in 4 cases. Conclusion: Most of the characteristics are consistent with previous studies with differences in few. Lichen planus is a chronic disease where treatment is directed to control of symptoms. Long-term follow-up is essential to monitor for symptomatic flare ups and possible malignant transformation.